A proposed guide for accreditation of teacher education in developing countries (A descriptive analytical study) (Kajian deskriptif analitikal tentang cadangan panduan akreditasi pendidikan guru di negara membangun) - Mahasin, (Penerbit UKM, 2011)
High quality education can only be delivered by high quality institutions that are well established to meet with today’s quality challenges. Thus, the present study strongly advocates for accreditation of Teacher Education in developing countries. The study aims to introduce a guide for accrediting Teacher Education that is hoped to serve as a common reference authority for Teacher Education institutions in developing countries.This aim also embraces the following objectives: to explore the main concepts, objectives, methods and procedures of accrediting Teacher Education, to explain the rationales of accrediting Teacher Education, to illustrate international evaluation measures of accrediting Teacher Education, to explore some models of various focuses of Teacher Education accreditation and to present standards of Teacher Education accreditation proposed to be applicable in developing countries.The study used the descriptive analytical method that describes the phenomena and participates in its analysis. To achieve the optimum advantage of the proposed guide, each institute of Teacher Education should utilize it according to its own mission, vision, and objectives.This guide is perceived to be a pertinent platform for Teacher Education institutions in developing countries to exchange innovative ideas, issues of common concern and to foster accreditation network among them. Although developing countries have various histories, cultural backgrounds, colonial experiences and political orientations but these notwithstanding they have common basic philosophy, goals, objectives and challenges regarding quality education and its recognition. The guide has been made transparent in order to increase its flexibility, validity and portability.